Association between Phytoestrogen Consumption and Female Reproductive Health: A Systematic Review of Experimental Models - Suhaimi, Nur Nadhirah; Waras, Maisarah Nasution; Ansor, Nurhuda Mohamad (Ibnosina Journal of Medicine and Biomedical Sciences, 2023)
Phytoestrogens have been shown as promising therapeutic agents for the treatment of menopausal symptoms, osteoporosis, breast cancer, and cardiovascular diseases. However, due to its unique chemical structure, phytoestrogen may cause unintended estrogenic and/or antiestrogenic effects on the human body, especially with regard to female reproductive health and performance. Hence, this systematic review aims to provide a critical evaluation of in vitro and in vivo evidence from the literature regarding the adverse effects of phytoestrogens on female reproductive health. The literature search was performed on four electronic databases including Scopus, Science Direct, PubMed, and Google Scholar following the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. A total of 965 studies were screened but only 58 of them were found to be relevant and assessed for eligibility. Of these, 23 studies met the eligibility criteria while the remaining studies were excluded due to insufficiently described methods and lack of clear findings being reported. From the review, phytoestrogens may alter the development of reproductive organs, prolong the estrus cycle, induce the accumulation of fluid in the uterus, and inhibit ovulation. The concentration and exposure duration of phytoestrogens may have different effects on the reproductive organs. Thus, further studies are warranted on the toxicodynamic, toxicokinetic, mode of action, and mechanism of actions of phytoestrogens on the female reproductive system to establish recommendations regarding phytoestrogen supplement consumption for women.
Keywords: estrogen; female reproductive organs; phytoestrogen; reproductive health